Strategi Guru Mengenalkan Konsep Dasar Literasi di PAUD sebagai Persiapan Masuk Sekolah Dasar - Fitriani, Ana; Rukhiyati, Iit; listiani, Meri; Sumiyati, Sumiyati; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
To prepare children for elementary school, it is crucial to learn the basic concepts of literacy from an early age. Teacher strategies are an essential element in the learning process. Introducing basic literacy concepts to early childhood provides a foundation for their transition to the next level of education. Furthermore, children are also expected to understand the concept of literacy. The purpose of this study was to determine teachers' strategies for introducing basic literacy concepts in early childhood education (PAUD) as preparation for entering elementary school. The research method used was a systematic literature study. The focus of the study was to search, select, and analyze various scientific sources related to early literacy and learning strategies in PAUD. The results showed that teachers used several strategies to introduce basic literacy concepts, including direct learning strategies or through play, involving children in learning activities, role-playing, storytelling, or storytelling.